Analisis Pengendalian Persediaan Bahan Baku Kacang Koro pada Produk Abon Menggunakan Metode Economic Order Quantity dan Desain Kemasan di UMKM Surya Abon - Rahmad Fauzi; Riky Ardiyanto; Roni Andika; Widya Setiafindari (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
This research aims to produce compatibility between the policies of Abon Surya with the Economic Order Quantity raw material control method, namely the purchase quantity of the Abon Surya policy has an average purchase of 770 kg, for the frequency of purchasing raw materials for jack beans 5 times, for security and point supplies. There is no reordering policy with a total inventory cost of IDR 251,640. Meanwhile, the EOQ method has an average purchase of 1,313 kg. the purchase frequency is only 3 purchases, the security inventory is 90 Kg and the number of reorders is 204 Kg with a total cost of inventory required of IDR 173,254. The cost difference between Abon Surya and the EOQ method is IDR 78,386,417. This shows that there is a saving or reduction in the total cost of inventory needed if Abon Surya can implement the EOQ raw material control method. Apart from that, the packaging used at UMKM Surya Abon for shredded products still uses transparent plastic with stickers, which is less attractive to buyers. Therefore, a new design is needed to attract more buyers.